Association between parental socio-demographic factors and declined linear growth of young children in Jakarta (Medical Journal of Indonesia, 2017)
Background: In Indonesia, approximately 35.5% of children under five years old were stunted. Stunting is related to shorter adult stature, poor cognition and educational performance, low adult wages, lost productivity, and higher risk of nutrition-related chronic disease. The aim of this study was to identify parental socio-demographic risk factors of declined linear growth in children younger than 2 years old. Methods: This was a cohort-prospective study between August 2012 and May 2014 at three primary community health care centers (Puskesmas) in Jakarta, Indonesia, namely Puskesmas Jatinegara, Mampang, and Tebet. Subjects were healthy children under 2 years old, in which their weight and height were measured serially (at 6–11 weeks old and 18–24 months old). The length-for-age based on those data was used to determine stature status. The serial measurement was done to detect growth pattern. Parental socio-demographic data were obtained from questionnaires Results: From the total of 160 subjects, 14 (8.7%) showed declined growth pattern from normal to stunted and 10 (6.2%) to severely stunted. As many as 134 (83.8%) subjects showed consistent normal growth pattern. Only 2 (1.2%) showed improvement in the linear growth. Maternal education duration less than 9 years (RR=2.60, 95% CI=1.23–5.46; p=0.02) showed statistically significant association with declined linear growth in children. Conclusion: Mother with education duration less than 9 years was the determining socio-demographic risk factor that contributed to the declined linear growth in children less than 2 years of age.